Effect of Drying and Size Reduction Techniques on the Characteristic of Instant Seasoning for Shredded Fish - Sela Julita; Dewi Sartika; Gusri Akhyar; Sri Hidayati; Subeki Subeki (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Instant seasoning for spiced shredded fish is practical and serves to expedite the process of producing shredded fish products. Instant seasoning has a potential to be developed and needs to be studied because it has not been found in the nearest supermarket. The objective of this study is to analyze and evaluate the quality of instant seasonings produced using various drying and size reduction techniques. The research was performed according to Completely Randomized Block Design, comprising two factors (i.e. drying techniques and size reduction techniques) and three replicates. Data was analyzed using the LSD (Least Significant Difference) and de Garmo tests to determine the most effective treatment. Seasoning quality was based on sensory attributes, chemical parameters, and microbiological parameters. The findings indicated that the application of drying and size reduction techniques had a discernible impact on the quality of instant seasoning for spiced shredded fish. The P3A1 (drying using food dehydrator and size reduction using chopper) treatment was determined to be optimal with 5.27% moisture content of, 8.57% fiber content, 42.88% free radical inhibition activity, 2.42 log CFU/ml total microbes, and 4.16 of score for overall acceptance.